Characterization of changes in the intestinal microbiome following combination therapy with zinc preparation and conventional treatment for children with rotavirus enteritis - Xu, Ning; Zhang, Wen; Huo, Jingjing; Tao, Rui; Jin, Taicheng; Zhang, Yuanmou; Wang, Yanjiao; Zhu, Lei; Li, JiaJia; Yao, Qi; Ge, Li (Frontiers in Cellular and Infection Microbiology, 2023)
Background: Rotavirus (RV) is one of the most common pathogens causing diarrhea in infants and young children worldwide. Routinely, antiviral therapy, intestinal mucosa protection, and fluid supplementation are used in clinic, however this is not efficacious in some severe cases. Zinc supplementation has previously been shown to improve resolution of symptoms from infectious diarrhea. Methods: In this study differences in response rate, duration of hyperthermia, vomiting, and diarrhea, and the persistence time of cough and lung rales in groups were compared. 16SrDNA gene sequencing technology was used to analyze and compare changes in the intestinal microflora of children with RV enteritis who received the conventional treatment with or without the zinc preparation. In addition, the correlations between the differential bacterial species and the related inflammatory factors were determined. Results: Conventional therapy combined with the zinc preparation significantly shortened the duration of hyperthermia, vomiting, and diarrhea compared with the conventional treatment alone. In addition, the time to symptom relief showed that the absorption time of cough and lung rales was significantly shorter in the combination treatment group than that in the conventional treatment group in the children with pneumonia. Further, compared with the conventional treatment, the combined treatment significantly increased the diversity and abundances of florae as compared with the conventional treatment. This combination therapy containing zinc preparation markedly increased the abundances of Faecalibacterium, Bacteroidales, Ruminoccoccoccus, and Lachnospiraceae at the genus level. The LEfSe analysis suggested that Clostridiumbolteae were most significantly altered after the combination therapy. In addition, a correlation analysis revealed significantly negative correlations between the inflammatory factors especially IL-6, TNF-a, CRP and some intestinal florae such as Bacteroides, Faecalibacterium, Blautia, Parabacteroides, Subdoligranulum, and Flavonifractor. Conclusion: Compared with the conventional therapy alone, the combined therapy with the zinc preparation significantly improves symptoms caused by RV. The combination therapy containing the zinc preparation significantly increases the diversity and abundances of some beneficial groups of bacteria. Further, The presence of these groups was further negatively correlated with relevant inflammatory factors. More importantly, this combination therapy containing the zinc preparation provides a reference for the clinical management of children with RV enteritis.